Analysis of Teacher Social Competency Development at SMP IT Nurul Fadhilah - Syahbanda, Rezi; Silalahi, Khairul Amri; Hanifah, Fathia; Munawwarah, Tarisa; Al-fahira, Nurasha; As’ari, Muharil; Sulaeman, Hasmar; Nasution, Inom (IKAMAS: Manajemen Pendidikan Islam, 2023)
Abstract : One of the keys to educational success is the teacher. Teachers play an important role in the learning process to improve the quality of students. Therefore professionalism a teacher is very important to note. Professional teachers are those who are able carry out their duties as educators to the maximum by having the ability and skills as an educator. This research is library research. The theory is obtained from library data then studied and analyzed in obtaining data conception to obtain objective results. The results of this study are for find out whether the teachers at SMP IT NURUL FADHILAH have implemented and develop social competence.